The ozonolytic synthesis of acetophenone - a by-product for the production of drugs of calming effect - A. H. Halstian; A. S. Bushuiev; V. V. Kotova; O. O. Demchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
Acetophenone is an important by-product for the manufacture of drugs of calming effect. Known methods of its production don't have the future due to technological complexity, harsh synthesis conditions and low processing coefficients of raw materials. Therefore, the development of low-waste, low-temperature synthesis of acetophenone with ozone is an urgent task.